2017
DOI: 10.5958/0974-8164.2017.00093.4
|View full text |Cite
|
Sign up to set email alerts
|

Groundnut productivity and profitability as influenced by weed control measures

Abstract: during Kharif seasons of 2015 and 2016 to test the efficiency of herbicides in groundnut. The experiment comprised of 14 weed control treatments arranged in randomized block design (RBD) with three replications. Among the different herbicides tested, imazethapyr + pendamethalin 1000 g/ha recorded lowest weed density and weed biomass of both broadleaved and grassy-weeds and significantly highest dry matter accumulation, number of pods/plant, pod, haulm and biological yield in groundnut over all the other herbic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Nanher et al, (2015) reported that the increased values in yield attributes of wheat crop might have been due to negligible weed crop-competition and increased nutrients and water uptake by the crop leading to increased rate of photosynthesis, supply of photosynthates to various metabolic sinks might have favoured yield attributes and overall improvement in vegetative growth which favorably influenced the tillering, flowering, fruiting and ultimately resulted in increased grain weight. These findings are in line with those reported by Singh and Saha, (2001), Yadav et al (2001) and Jat et al (2003).…”
Section: -Grain Weightsupporting
confidence: 93%
“…Nanher et al, (2015) reported that the increased values in yield attributes of wheat crop might have been due to negligible weed crop-competition and increased nutrients and water uptake by the crop leading to increased rate of photosynthesis, supply of photosynthates to various metabolic sinks might have favoured yield attributes and overall improvement in vegetative growth which favorably influenced the tillering, flowering, fruiting and ultimately resulted in increased grain weight. These findings are in line with those reported by Singh and Saha, (2001), Yadav et al (2001) and Jat et al (2003).…”
Section: -Grain Weightsupporting
confidence: 93%
“…This resulted in poor growth of weeds and suppressed the newly developing leaves within 48 h after the application herbicide and complete damage of weeds within 6 days after the application of herbicide. Similar results were reported by Singh et al (2017Singh et al ( , 2020.…”
supporting
confidence: 91%
“…This might be due to the fact that weed free environment in crop facilitated better peg initiation and development at the critical growth stages of groundnut which ends to increase in number of pods/plant and pod yield. Singh et al (2017) also reported the beneficial effect of preemergence application of pendimethalin 1000 g/ha followed by post-emergence application of imazethapyr 75 g/ha in lowering weed density and weed biomass of both broad-leaved and grassyweeds and significantly increasing dry matter accumulation, number of pods/plant, pod yield, haulm yield and biological yield in groundnut over all other herbicidal treatments.…”
Section: Effect On Cropmentioning
confidence: 92%